Augmented Reality Based Tajwid Reading Law Android Application - Agyztia Premana (Brilliance: Research of Artificial Intelligence, 2023)
The learning method used in learning the subjects of the Qur'an and Hadith in Schools is a common teaching method, which uses books as a source of knowledge and teachers as teachers. In this problem, the author uses a learning method using Augmented Reality (AR) as the basic law of reading aloud so that students don't get bored. Augmented Reality (AR) is a combination of real and virtual objects displayed simultaneously on a screen. Augmented Reality is created with Unity 3D, Vuforia and Android software. The application of new learning methods should increase students' interest in serious and straightforward learning. This research aims to build a recitation science learning application for children 5-10 years old using an Android-based device "so that with this application it is hoped that it will have an attractive design, as well as complete features and have materials and examples of legal reading and pronunciation." easy for children to understand and can make children understand the science of recitation from a young age. The results of this research are applications for learning the science of Tajweed for children 5-10 years old which can display the hijaiyah letters accompanied by their pronunciation and how to pronounce them, the laws of the science of Tajweed which consist of the law of nun mati/tanwin, qalqalah and the law of mad, games as material for evaluating children. The Tajwid science learning application succeeded in increasing children's understanding of Tajweed science by 57.9%. Application feasibility testing uses white box and black box methods with several test requirements. Based on the test results, functionally the application is appropriate, feasible, and can be used as a learning medium for Tajwid science and is in the "Very Good" category.